Development of Digital Teaching Material Based on Numeracy For 4th Class Primary School - Nabela, Silvio Juliana; Agustine, Putri Cahyani (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
Indonesian students' mathematical literacy abilities are at a low level. Students have not been able to solve problems that require logical and applied thinking. So, teaching materials are needed that can facilitate critical thinking skills based on numeracy literacy which refers to 21st century learning by optimizing technology in learning. The teaching materials developed refer to several mathematical applications such as facts, operating principles, and problem solving in everyday life. The research method used in this research is Research and Development (R&D) with the ADDIE model consisting of Analysis, Design, Development, Implementation and Evaluation. The research results show that digital teaching materials are suitable for use based on validation results by material experts, media experts and language experts. Practical digital teaching materials are used based on the results of teacher and student response questionnaires.